Developing a Real-Time Trophic State Index of a Seawater Lagoon: A Case Study From Dapeng Bay, Southern Taiwan - Chen, Chung-Chi; Wang, Jih-Terng; Huang, Chih-Yen; Hsieh, Hung-Yen; Tew, Kwee Siong; Meng, Pei-Jie (Frontiers in Marine Science, 2022)
Algal blooms over the past years have caused considerable worldwide impacts on marine ecology, aquaculture, recreational activities, and human health. Therefore, there is an urgent need to develop indices for evaluating the nutritional status of seawater as a means of predicting algal blooms. A long-term water quality monitoring dataset from Dapeng Bay, Southern Taiwan, indicated that seawater dissolved oxygen (DO) concentrations and pH were significantly correlated with algal abundance. Using this dataset, we then developed a real-time trophic state index (RTSI) by (1) referring to the seawater nutrient grading system defined by Carlson’s index and (2) incorporating an algorithm based on the relationship between DO, pH, and eutrophication status. The RTSI was superior to contemporary indices in its simplicity, as no complicated nutrient or chlorophyll a (Chl a) measurements were required, and real-time data were displayed on a personal computer. The index is sensitive to changes in seawater quality that will be of aid to managers.